Church, Kingship, and Lay Investiture in England, 1089-1135 - Cantor, Norman F., eauthor (Book collections on Project MUSE., 1958)
In the latter part of the eleventh century a revolutionary group within the Western Church, centered in the papacy, attempted to overthrow the early medieval system of church-state relations by which the church in each country was under control of the kings and other secular rulers. Here is a comprehensive history of these controversies during the crucial period from the death of Archbishop Lanfranc in 1089 to the end of the reign of Henry I in 1135. The greater part of the book is concerned with the pontificate of Archbishop Anselm (1093-1109) and includes the first substantial account of the episcopal career of this famous theologian. In a concluding chapter, the obscure period in the history of the English Church from 1109 to 1135 is investigated, and the methods by which Henry I reasserted royal authority over the Church are indicated.Originally published in 1958.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.